National Athletic Trainers' Association position statement: Conservative management and prevention of ankle sprains in Athletes - Kaminski, T. W.; Hertel, J.; Amendola, N.; Docherty, C. L.; Dolan, M. G.; Hopkins, J. T.; Nussbaum, E.; Poppy, W.; Richie, D. (Journal of Athletic Training, 2013)
Objective: To present recommendations for athletic trainers and other allied health care professionals in the conservative management and prevention of ankle sprains in athletes. Background: Because ankle sprains are a common and often disabling injury in athletes, athletic trainers and other sports health care professionals must be able to implement the most current and evidence-supported treatment strategies to ensure safe and rapid return to play. Equally important is initiating preventive measures to mitigate both first-time sprains and the chance of reinjury. Therefore, considerations for appropriate preventive measures (including taping and bracing), initial assessment, both short- and long-term management strategies, return-to-play guidelines, and recommendations for syndesmotic ankle sprains and chronic ankle instability are presented. Recommendations: The recommendations included in this position statement are intended to provide athletic trainers and other sports health care professionals with guidelines and criteria to deliver the best health care possible for the prevention and management of ankle sprains. An endorsement as to best practice is made whenever evidence supporting the recommendation is available.